Corporate Identity Canting Buana Kreatif: Rancangan dan Pengaplikasiannya - Izan Qomarats; Eva Y. (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2020)
Canting Buana Kreatif is a small and medium-sized business that is developing towards an international scale company. This company is engaged in the creative industry (Batik Tanah Liek, a Minangkabau heritage). With the opportunities offered by the market which is quite tempting, making Widdi, the owner of Canting Buana Kreatif wants to make a Corporate Identity that is attractive, memorable and can fully represent the vision, mission and goals of his company. The goal is that the company has a positive image as a whole and can become better known and have a stronger identity in its market place. Corporate identity is created and applied to promotional media in accordance with the character of the target audience and the target market “canting buana creatives”. The method used to design this corporate identity is a qualitative method with an emphasis on Cyclic Strategy through several stages of the process, namely: briefs, problem seeking, analysis and solutions. After a solution is found, then proceed to the pre-production, production, post-production and evaluation stages. It is hoped that “Canting buana creatively” will be the only best place to visit when you want to recognize and understand Minangkabau batik.ABSTRAKCanting Buana Kreatif merupakan usaha kecil menengah yang berkembang menuju perusahaan skala International. Perusahaan ini bergerak di lingkup industri kreatif (Batik Tanah liek warisan Minangkabau). Dengan peluang yang ditawarkan pasar yang cukup menggiurkan, membuat Widdi yaitu owner Dari Canting Buana Kreatif ingin membuat Corporate Identity yang menarik, memorable dan dapat mewakili sepenuhnya visi, misi dan tujuan perusahaannya. Tujuannya agar perusahan memiliki citra positif secara menyeluruh dan dapat menjadi lebih dikenal serta identitasnya menguat di market place nya. Corporate identity dibuat dan diaplikasikan pada media promosi yang sesuai dengan karakter dari target audience dan target market Canting Buana Kreatif. Metode yang digunakan untuk merancang corporate identity ini adalah metode kualitatif dengan penekanan ke Cyclic Strategy melalui beberapa tahapan proses, yaitu: brief, problem seeking, analysis dan solusi. Setelah solusi ditemukan, barulah dilanjut ke tahap pra-produksi, produksi, pasca produksi dan evaluasi. Diharapkan Canting Buana Kreatif nantinya akan menjadi satu-satunya tempat terbaik yang akan dikunjungi ketika ingin mengenali dan memahami batik Minangkabau.Kata Kunci: Corporate, Identity, Batik, Minangkabau